Low-dose dental irradiation decreases oxidative stress in osteoblastic MC3T3-E1 cells without any changes in cell viability, cellular proliferation and cellular apoptosis - Pramojanee,S.N. (Elsevier Limited, 2015)
Cellular responses following low-dose irradiation have been widely debated. Several studies have revealed detrimental effects of low-dose irradiation; however, some studies have shown contrasting results. Moreover, the effects of periapical irradiation on osteoblastic cells have not yet been revealed. Therefore, in this study, we tested the hypothesis that low-dose dental irradiation of osteoblastic cells reduces reactive oxygen species (ROS) production and leads to increased cellular proliferation and high-dose dental irradiation of osteoblastic cells increases ROS production and leads to cellular apoptosis. Methods: We irradiated MC3T3-E1 cells with various doses of periapical irradiation (0, 1, 2, 5 and 10 doses, 1.5 mGy/dose). We evaluated cell viability using MTT assay, the expression of Bax and Bcl-2, as markers for apoptosis and the expression of cyclin D1 as a marker for cell proliferation 24 h after each irradiation. We also measured ROS production 4 h following each irradiation. Results: ROS production was significantly reduced after one dose of periapical irradiation (1.5 mGy); however, after 10 doses (15 mGy), ROS production was significantly increased (p < 0.05). None of the doses of dental radiation affected cell viability as determined by MTT assay, nor did they change the apoptotic marker: (the Bax/Bcl-2 ratio). However, 10 doses of dental irradiation significantly decreased the expression of cyclin D1. Conclusions: Our findings suggest that low-dose dental radiation may help to detoxify osteoblastic cells by reducing ROS production without any changes in cell viability, cellular apoptosis or proliferation. However, high-dose dental radiation impairs osteoblastic proliferation via increase ROS production without any changes in cell viability or apoptotic responses. © 2011 Elsevier Ltd.